Abd el-Kader o XIX-wiecznej Europie - Gadamska-Serafin, Renata (Tematy i Konteksty, 2018)
As a consequence of being an Algerian leader in the struggle of the independence movement and anti-colonial war against France during the 19th century, Emir Abd el-Kader spent 5 years in a French prison. Later he visited Paris and other European cities on other occasions as well. These events in el-Kader’s life were excellent opportunities to become well acquainted with Western civilization. His work: Call to the Intelligent, Warning to the Indifferent. Philosophical, religious, historical and related considerations (Paris 1858) can be described not only as a philosophical work but also as a tactful worldview discussion and a well-balanced, though a little covert, critique of the modern civilization and Western Culture. Despite his enthusiasm for Western culture and its intellectual trends of the time, the Arab thinker saw the profound flaws in the modern, Cartesian rationalism. Being a true adherent to the Eastern beliefs of reason and religion as inseparable entities, el-Kader advocated their alliance also in the field of science. He regarded religion and science as complementary domains. He also reproached European scholars for the rejection of tradition as a source of truth, which he perceived as a mistake. During the time of colonial politics, which was based on political and religious confrontation, el-Kader wrote about the essential unity of all religions and a need for consensus between people of all creeds around uniform values. Abd el-Kader’s work remains to this day an interesting testimony of the 19th-century Europe’s reception by a true Eastern thinker coming from the world of Islam.